Novel primers of Cyt b sequencing for a non-invasive genetic assessment of the Silvery Gibbon (Hylobates moloch) - ADIFA RISA BAGASTA; SUNARTO SUNARTO; ARI SUSILOWATI; SURATMAN SURATMAN; DWI SENDI PRIYONO; MOHAMMAD SAIFUL MANSOR; PUGUH KARYANTO (Society for Indonesian Biodiversity, 2026)
Abstract. Bagasta AR, Sunarto, Susilowati A, Suratman, Mansor MS, Priyono DS, Karyanto P. 2026. Novel primers of Cyt b sequencing for a non-invasive genetic assessment of the Silvery Gibbon (Hylobates moloch). Biodiversitas 27 (1): d270101. https://doi.org/10.13057/biodiv/d270101. Reliable primers for genetic variation assessment of the silvery gibbon (Hylobates moloch) are still unavailable. This study aims to design novel primers for the silvery gibbon's complete Cytochrome b (Cyt b) to facilitate a non-invasive genetic variation assessment. Three primer pairs targeting different regions of Cyt b were designed using Primer3Plus and validated through in-silico validation by adjusting a melting temperature (Tm) between 57-63°C and a GC content of 45-65%, and in vivo validation using Sanger sequencing. The primers were optimized for annealing temperature. The optimum annealing temperatures used in this research were 55°C for T1 and T3, and 52°C for T2, and were tested against DNA from ten gibbons' feces collected from the northwestern part of the Dieng Plateau. The gel electrophoresis results showed the amplification success, indicated by the DNA band visualization above 900 bp. Our primers successfully amplified the target, producing 625-1068 bp. De novo assembly on the obtained sequences yielded a range of fragment lengths of 1857-1950 bp and successfully assembled the complete Cyt b gene of 1140 bp. Single-nucleotide polymorphisms (SNPs) were readily detected at sites 67, 222, 234, 271, 286, 364, 372, 378, 501, 563, 918, and 991 (12 sites) along the Cyt b gene of the ten samples of silvery gibbons. We also successfully observed five haplotypes amongst the entire sample. This success indicates that our primers effectively sequence the Cyt b gene of the silvery. Our primers perform a highly resolution ability to assess variation amongst populations, making them a valuable tool for non-invasive population genetic assessment supporting the silvery gibbon's conservation program.